กรณีศึกษาการประยุกต์ใช้การศึกษาวิธีทำงานกับงานก่อสร้างบ้านจัดสรร - ศิริชัย มังคละอภินันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The research aims to study the obstacles of applying method study in housing construction projects. The obstacles are identified in each step of applying method study to present the characteristics of method study which leads to work success. The methodology started with collecting data from the case study. The method of data collection is divided into 3 parts. The first part uses the questionnaire for collecting the general data of the project. The second part uses the observation and monitoring work practice in the monitored activities by using the subjective judgment from researcher in order to understand the factors and procedure of work. The third part uses the questionnaire for collecting data regarding the opinion of related persons about the factors that affect the success of method study application. The results revealed that the obstacles in "defining problem" step are agreement with the objective of development and unsuitable prioritizing of work, which is a result of human factor. The obstacles in "data recording" step are the process data from the model project not reflecting other projects, a result of management factor. The obstacles in "analysis and developing alternatives" step are the long duration used in reaching satisfied conclusion and lack of cooperation in development, a result of human factor. Finally, the obstacles in "implementing and maintaining" step are the difficulty in applying the same standard of implementation and lack of obtaining continuous monitoring of the application results.